INSERTION OF A MICRO-PERFORATED PANEL TO IMPROVE SOUND TRANSMISSION LOSS OF A DOUBLE-LEAF PARTITION - Putra, Azma; Ismail, Ahmad Yusuf; Ayob, Md Razali (Universiti Teknikal Malaysia Melaka, 2012)
Over decades a double-leaf partition in engineering structures has been widely applied for its advantages i.e. in terms of the mechanical strength and toughness as well as its lightweight property. For noise control application, the double-leaf has also been known to be an effective noise barrier. Unfortunately at resonance frequency, the sound transmission loss (TL) reduces significantly due to the coupling between the panels and the air between them. This paper investigates the effect of a micro-perforated panel (MPP) inserted inside a double-leaf partition to improve the TL performance at the troublesome resonance frequency of a conventional double-leaf structure. It is found that the TL improves at the resonance if the MPP is located closer to the solid panel. The mathematical model is derived for normal incidence of acoustic loading.